Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

Thermophilic temperature of 70–80°C optimizes co-reduction of metal bioavailability and antibiotic resistance genes via microbially-associated stabilization and suppressed host-ARG co-occurrence - Xiaoxia Hao; Xueyao Sun; Fengshuo Yu; Shuyue Zhang; Hongxi Qian; Li Zhu; Lin Bai (Bioresource Technology, 2026)

Biostratigraphic and paleobiogeographic significance of two cap-shaped fossil groups from the Cambrian Xinji Formation, North China: Evidence for North China–Australia faunal links - Meng Gong; Hong Hua; Yang Hou; Xinzi Wang; Song Zhang; Zihui Wu; Xueting Wang; Ling Yu; Yan Tan; Jinzhou Luo; Lin Bai (Journal of Asian Earth Sciences, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

A new biostratigraphic marker for Cambrian Stage 3 on the Northern Margin of the Yangtze Platform: Mianxiantubus–Pelagiella subangulata assemblage subzone - Xueting Wang; Hong Hua; Jinzhou Luo; Yang Hou; Meng Gong; Song Zhang; Xinzi Wang; Zihui Wu; Yan Tan; Ling Yu; Lin Bai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Development of a Recombinant Goose Parvovirus VP2 Neutralizing Epitope-Containing Region Vaccine Adjuvanted with IL-2 and FliC for Enhanced Immune Responses and Protection Against Challenge - Qing Wu; Xinyu Li; Jiaxin Li; Ziran Liu; Lin Bai; Lin Zhang; Shujing Xia; Di Wu; Yuhan Jin; Xinyuan Shen; Yu Gao; Jingming Wang; et al. (The Veterinary Journal, 2026)

Dynamic characteristics and accumulated plastic deformation prediction of lithium slag filler for road applications based on interpretable machine learning - Hai Shi; Zhenghao Yu; Xiangjin Ji; Kun Yu; Mingzhou Bai; Daming Lin; Yin Cheng (Soil Dynamics and Earthquake Engineering, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

Context-dependent coupling between rhizosphere biochemical activation and SOC enrichment in croplands: a global meta-analysis - Ya-Jun Cheng; Jie-Yu-Xin Kang; Chun-Yan Li; Bai-Jian Lin; Yun Zhang; Jian-Ying Qi (Plant and Soil, 2026)

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Multifunctional BQD interlayer enables high-resolution high-efficiency QLEDs:Eliminating EML void defects and optimizing interfacial carrier transport - Yue Chen; Yuting Bai; Zunxian Yang; Luxi Yuan; Ye Chen; Xudong Jiang; Jiajie Hong; Benfang Liu; Zhiyu Yuan; Jinzhu Gao; Zhezhou Fang; Runsen Yu; et al. (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Subduction-controlled Late Triassic rifting along the northern margin of Gondwana - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Yang Wang; Jun-Pu Lv; Xin-Yu Hou (International Geology Review, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Targeted metabolomics analysis for discriminating geographical origin of Chardonnay grape and wine at sub-regions in China's Ningxia: Terroir effect - Xiaofeng Yue; Yang Zhang; Xinran Bai; Bo-chen Liu; Yu-lin Fang; Yan-lun Ju (Food Research International, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

A novel urban boundary layer model integrating lidar measurement and physical equation constraints - Yue Xu; Yi Yang; Xianfeng Yu; Baojun Bai; Kunbo Wen; Lijun Yuan; Xinjun Lin (Urban Climate, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Stable neodymium isotopic composition of the upper continental crust through time from ancient glacial diamictites and Holocene marine sediments - Xiaoxiao Yu; Jianghao Bai; Gangjian Wei; Mang Lin; Roberta L. Rudnick (Geochimica et Cosmochimica Acta, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

Dual-Interface engineering and solvation structure regulation enable polyether based semi-solid polymer electrolyte in high voltage lithium metal battery - Yu-Jie Ren; Pei-Pei Chen; Kuan-Kuan Tian; Bai-Qin Xiong; Dong-Lin Zhao (Chemical Engineering Journal, 2026)

Obstacle avoidance path tracking control for underwater tracked robots with path-dependent constraints - Xiaolong Yao; Kelin Feng; Kewen Li; Yongming Li; Yu Wang; Xuejian Bai; Wenxing Sun; Yazhou Fan; Zheng Wang; Guohai Lin (Ocean Engineering, 2026)

The synergistic effects of ammonium and phosphorus on higher alcohol biosynthesis in Zygosaccharomyces mellis LGL-1 and its application for wampee/grape winemaking - Chunyun Qu; Zuyue Qi; Shuochun Lin; Jianjun Li; Yu Zeng; Yiyin Xu; Weidong Bai; Gongliang Liu (Food Microbiology, 2026)

Multi-material vibration attenuation metastructure under multidirectional loads - Yu Li; Lin Li; Cuiping Bai; Zhidong Liu; Hualin Fan (Engineering Structures, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Visco-elastic interface and dynamic response of a lined tunnel in anisotropic rock mass under unloading waves - Xue-Qian Fang; Zhao-Feng Zhong; Bai-Lin Li; Xin-Yu Liu; Ya-Wen Xiong (Soil Dynamics and Earthquake Engineering, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Early evolution of the Meso-Tethys Ocean: Constraints from Permo-Triassic flysch deposits - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yang Wang; Li-Qiang Zhang (Gondwana Research, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Evaluation of the multi-scale variability of ocean bottom pressure in a global ocean general circulation model - Jiahui Bai; Jingwei Xie; Zipeng Yu; Jiangfeng Yu; Hailong Liu; Fan Yang; Pengfei Lin; Tao Zhang; Chunxiang Shi; Yun Xiao (Acta Oceanologica Sinica, 2026)

Skin Ulceration in Farmed Leopard Coral Grouper (Plectropomus leopardus) Was Associated with Vibrio spp. and Photobacterium damselae in China - Yunji Xiu; Xiaowan Lin; Lirong Jiang; Zemin Bai; Jinlong Dong; Jinjing Cao; Xiuxiu Tian; Yu Zhang; Wei Wang; Ying Huang; Bo Zhou; Lei Wang; et al. (Fishes, 2026)
The leopard coral grouper (Plectropomus leopardus), an economically important marine fish, is widely farmed in Hainan Province, China. However, intensive farming has led to frequent disease outbreaks, including viral nervous necrosis, vibriosis, and enteritis, with skin ulceration a widespread and significant concern. To identify the pathogen causing skin ulceration, we collected diseased fish from Hainan and conducted histopathological and ultrastructural analyses, parasite examination, viral metagenomic sequencing, and bacterial isolation and identification. The histopathological analysis and ultrastructural observation showed that the diseased P. leopardus displayed marked pathological alterations, with significant hepatic degeneration and necrosis and splenic structural disorganization. Parasites and viruses were both excluded from being the primary pathogen. A total of 79 bacterial strains were isolated from diseased P. leopardus liver tissue, including Vibrio harveyi (38 strains, 48.1%), Vibrio owensii (17 strains, 21.5%), Vibrio rotiferianus (16 strains, 20.3%), and Photobacterium damselae subsp. damselae (8 strains, 10.1%). Infection experiments suggested that all four bacterial species could induce skin ulceration. This study demonstrates that skin ulceration in P. leopardus is associated with multiple bacterial pathogens, refining the previous view that attributed the disease solely to V. harveyi. These findings provide a foundation for developing vaccines and disease-resistant breeding strategies.

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Mechanical and microstructural degradation of pile-surrounding mudstone induced by dynamic pile driving: A multi-scale experimental study - Jichao Yin; Xiaoyu Bai; Nan Yan; Yamei Zhang; Lin Cui; Yu Cong; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Unraveling the impacts of climate factors on leaf area index of Chinese grasslands using interpretable machine learning models - Wei Liu; Chengxi Gao; Shaozhi Lin; Yu Zhou; Wenrui Bai; Junhu Dai; Huanjiong Wang (Theoretical and Applied Climatology, 2026)

Intercropping maize and soybean promotes specialized soil microbial communities and boosts carbon and nitrogen cycling in a semi-arid agroecosystem - Olatunde Pelumi Oladele; Shuo Yao; Ming-Zhu Huang; Yu-Gang Tian; Xin Zhao; Yash Pal Dang; Wei Bai; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Intercity red meat trade exacerbates the spatial inequality of greenhouse gas emissions and health burdens in China - Yue Zhao; Le Yu; Zhaohai Bai; Lin Ma (Journal of Environmental Management, 2025)

Trade of crop products contribute to the alleviation of global nitrate leaching risks - Xuchong Chen; Ling Liu; Yu Lu; Xuan Wang; Zhaohai Bai; Lin Ma (Global Environmental Change, 2025)

Glacial-interglacial climate modulates sedimentary sulfur cycling in the Peruvian oxygen minimum zone: Mechanistic insights from pyrite multiple sulfur isotopes - Xiaoxiao Yu; Fang Qian; Xiaomin Lin; Longye Du; Jianghao Bai; Dawei Lv; Yanguang Liu; Gangjian Wei; Mang Lin (Geochimica et Cosmochimica Acta, 2025)

Preparation of sodium alginate/sodium carboxymethyl cellulose composite coating film and evaluation of its effects on mango preservation - Wei Wang; Jiakai Yu; Yuting Huang; Bai-Jun Li; Wenzhu Shen; Wenli Zhang; Yining Xia; Qiong Lin (Food Chemistry, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Effects of Cyclic Thermal Stimulation on Granite Permeability and Mechanical Strength: Inspiration for the Enhanced Geothermal System - Yilong Yuan; Yu Wang; Tianfu Xu; Hongwu Lei; Hewen Bai; Lin Jiang; Taisen Wang; Zhiwu Xiong (Rock Mechanics and Rock Engineering, 2025)

Chicago Sky Blue 6B modulates MAPK/NF-kB pathway in rat knee osteoarthritis - Yejin Zhang; Weiqing Li; Yu Bai; Hehuan Lai; Jiawei Fang; Lin Ye; Dengwei He; Zhenzhong Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

High-resolution assessment reveals underestimated human health risks of ammonia emissions in China's pig production - Yue Zhao; Le Yu; Zhenrong Du; Zhaohai Bai; Ling Liu; Tao Liu; Lin Ma (Journal of Cleaner Production, 2025)

Integrated analysis of lncRNA-miRNA-mRNA regulatory network revealing molecular mechanisms of immune response and ion transport in Eriocheir sinensis under alkalinity stress - Jun-Lei Ma; Yu-Lin Bai; Yi-Dong Liang; Ting Zhang; Lei You; Dong-Po Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Association of air pollution exposure and habitual physical activity with risk of overall and cause-specific hospital-treated infections: a UK Biobank cohort study - Zixuan Jiang; Yahang Liu; Yifang Huang; Chen Huang; Yating Yang; Ruilang Lin; Jing Wang; Runzhi Bai; Xueying Zheng; Yongfu Yu; Guoyou Qin (Environmental Research, 2025)

Oxytocin Regulated Neuroinflammation through OTR/Mitochondria Mediated Pathway to Improve Hypoxia-Induced Brain Injury - Xiaomei Yang; Kai Li; Lin Chen; Lei Wang; Xuyang Wang; Kangping Lu; Yu Bai; Yonghao Hou; Jingchen Hou; Chao Wang; Xiaoyan Cheng; Joseph Oldam; et al. (Molecular Neurobiology, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Biodegradable Janus membrane for oil/water separation and unidirectional oil transport via electrospinning and plasma treatment - Hongshen Lin; Fangxia Yu; Jingxi Liang; Shenao Bai; Rongzong Cai; Pingfan Xu; Peikun Zhang; Yaofa Luo (Journal of Cleaner Production, 2025)

Portable miRNA profiling of sepsis-associated exosomes via a novel DNA molecular lock-mediated nanobiosensor - Wei Xie; Shu Jia; Rongjun Yu; Jianjiang Xue; Shulian Bai; Chenxing Wang; Gang Tian; Qiongyuan Zhang; Xiao Gui; Lilin Wang; Silin Chen; Ke Lin; et al. (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Nitrogen addition improved rhizosphere phosphorus availability and phosphorus-phytoextraction of Polygonum hydropiper through optimizing rhizosphere enzymes, microbial interactions and functions - Daihua Ye; Xiaoyu Bai; Min Xie; Yujie Li; Tao Liu; Lin Ji; Xizhou Zhang; Huagang Huang; Haiying Yu; Yu Tang; Yongdong Wang; Tingxuan Li (Plant and Soil, 2025)

A stable dual-functional monomer imprinted polymer platform for electrochemical sensitive detection of PFAS - Xingyang Cheng; Jing Tang; Yu Chen; Xue Bai; Yibo Liao; Xilian Ouyang; Yuchen Wang; Lin Tang (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Narrowband deep-blue polymer light-emitting diodes: Beneficial from the individual planar-conformational chain segment in hierarchically ordered nano-domain - Bin Liu; Jiangli Cai; Yingying Zheng; Yang Xu; Jinghao Yang; Wenyu Chen; Mengyuan Li; Ningning Yu; Mingjian Ni; Lubing Bai; Chongping Song; Lili Sun; et al. (Chemical Engineering Journal, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

The simulation of the South China Sea by the variable resolution version of the global ocean general circulation model LICOM3.0 - Jiangfeng Yu; Jingwei Xie; Hailong Liu; Pengfei Lin; Zipeng Yu; Jiahui Bai (Ocean Modelling, 2025)

Chemical constituents from Dendrobium huoshanense and their chemotaxonomic significance - Huan Liu; Hui Yang; Bai-Lin Su; Bo-Wei Li; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2025)

Deep multivariable spatial attention CNN-based spatial grid NWP error correction for accurate one-day-ahead photovoltaic power forecast - Mingliang Bai; Ruidong Wang; Chaojing Lin; Yunxiao Chen; Fuxiang Dong; Zhihao Zhou; Xusheng Yang; Jinfu Liu; Daren Yu (Earth Science Informatics, 2025)

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

Hand preferences in captive non-human primates are associated with generation and stress level - Lin Wang; Yunchao Luo; Haoyu Sun; Yiru Gu; Yu Wang; Yali Bai; Zhongqiu Li (Applied Animal Behaviour Science, 2025)

FengYun-3 meteorological satellites’ microwave radiation Imagers enhance land surface temperature measurements across the diurnal cycle - Yuyang Xiong; Tianjie Zhao; Haishen Lü; Zhiqing Peng; Jingyao Zheng; Yu Bai; Panpan Yao; Peng Guo; Peilin Song; Zushuai Wei; Ronghan Xu; Shengli Wu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Conformational entropy modulation of the work function for the construction of efficient ohmic contacts to accelerate the catalytic conversion of lithium polysulfide - Jing-Zhou Chen; Yu-Jie Ren; Kuan-Kuan Tian; Bai-Qin Xiong; Dong-Lin Zhao (Chemical Engineering Journal, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Nonconventional phosphorus-based tertiary amine curing agent enabling the high fire safety, outstanding tensile strength and high glass transition temperature of epoxy resin - Xue-Qi Chen; Yu-Cai Lin; Wei-Bin Bai; Yuan-Wei Yan; Rong-Kun Jian (Chemical Engineering Journal, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

A smartphone-based enhanced colorimetric immunoassay for the detection of Trichinella spiralis infection - Yao Yu; Lianjing Zhao; Nuo Xu; Xiaolei Liu; Lin Li; Ning Xu; Xue Bai (Veterinary Parasitology, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

Efficient removal of levofloxacin by FeCo2O4@C-REC activated peroxymonosulfate: Performance and mechanism - Bai-Hang Zhao; Bao-Yu Zhang; Bing-Lin Zhang; Jing Zhang; Chun Wang; Ye Li (Journal of Water Process Engineering, 2025)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

Differential mineral diagenetic evolution of lacustrine shale: Implications for CO2 storage - Liu Wang; Bo Liu; Longhui Bai; Lin Ma; Zhichao Yu; Qiuli Huo; Kevin G. Taylor (International Journal of Coal Geology, 2024)

Deep dehumidification characteristics of a silica gel coated cross-flow heat exchanger with a circulating blowing loop - Lin Liu; Hongyu Huang; Jun Li; Yu Bai; Zhaohong He; Lisheng Deng; Tieyu Gao; Mitsuhiro Kubota; Noriyuki Kobayashi (Energy and Buildings, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Investigation of factors affecting oil-water separation efficiency in micro-bubble micro-cyclonic flow air flotation - Wei Wang; Xiang Zhao; Xu Bai; Xue-liang Ma; Wei Lin; Jiu-yang Yu (Journal of Water Process Engineering, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Hotspot–subduction zone interactions and their resource effects at ∼120 Ma on the central Tibetan Plateau - Jia-Wei Bai; Jian-Jun Fan; Ye Zhan; Bo-Chuan Zhang; Si-Lin Sun; Yu-Jie Hao (Lithos, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Insight into response mechanism of aerobic granular sludge to combined nanoparticle stress: Nitrogen removal, microbial community and heavy metal resistance genes - Yu-Qi Li; Bai-Hang Zhao; Yu-Qing Zhang; Hai-Shan Yang; Bing-Lin Zhang (Chemical Engineering Journal, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Optimizing the rate of straw returning to balance trade-offs between carbon emission budget and rice yield in China - Ruo-Chen Li; Yu-Gang Tian; Fan Wang; Yuan-Feng Sun; Bai-Jian Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang; Zhi-Yu Xu (Sustainable Production and Consumption, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Late Jurassic–Early Cretaceous Rebangco ophiolite, Tibet: Constraints on the Meso-Tethys Ocean tectonic evolution - Jia-Wei Bai; Jian-Jun Fan; Yu-Jie Hao; Bo-Chuan Zhang; Si-Lin Sun (Journal of Asian Earth Sciences, 2024)

Waste treats waste: Facile fabrication of porous adsorbents from recycled PET and sodium alginate for efficient dye removal - Jing Yu; Lan Bai; Zijun Feng; Lin Chen; Shimei Xu; Yuzhong Wang (Chemosphere, 2024)

Investigation of bioactive compounds and their correlation with the antioxidant capacity in different functional vinegars - Hua Bai; Shuang Wang; Zong-Min Wang; Lan-Lan Zhu; Hong-Bo Yan; Yan-Bo Wang; Xin-Yu Wang; Lin Peng; Ji-Zhou Liu (Food Research International, 2024)

Blockade of aryl hydrocarbon receptor restricts omeprazole-induced chronic kidney disease - Nan Sun; Yimeng Zhang; Lin Ding; Xin An; Fang Bai; Yanjiang Yang; Kuipeng Yu; Jiahui Fan; Lei Liu; Huimin Yang; Xiangdong Yang (Journal of Molecular Medicine, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Sequential starch modification by branching enzyme and 4-α-glucanotransferase improves retention of curcumin in starch-alginate beads - Yu Wang; Chengfang Pang; Hossein Mohammad-Beigi; Xiaoxiao Li; Yazhen Wu; Marie Karen Tracy Hong Lin; Yuxiang Bai; Marie Sofie Møller; Birte Svensson (Carbohydrate Polymers, 2024)

Estimating leaf age of maize seedlings using UAV-based RGB and multispectral images - Yi Bai; Liangsheng Shi; Yuanyuan Zha; Shuaibing Liu; Chenwei Nie; Honggen Xu; Hongye Yang; Mingchao Shao; Xun Yu; Minghan Cheng; Yadong Liu; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Plant selection and ecological microhabitat drive the shrub-associated microbiome selection in revegetated shrub ecosystems - Zongrui Lai; Yanfei Sun; Yang Yu; Zhen Liu; Yuxuan Bai; Yangui Qiao; Lin Miao; Weiwei She; Shugao Qin; Wei Feng (Applied Soil Ecology, 2023)

Polyphenolic glycosides with unusual four-membered ring possessing anti-Parkinson's disease potential from black wolfberry - Yi-Kao Hu; Xiao-Lin Bai; Guang-Yu Shi; Yong-Mei Zhang; Xun Liao (Phytochemistry, 2023)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

Quantifying effect of maize tassels on LAI estimation based on multispectral imagery and machine learning methods - Mingchao Shao; Chenwei Nie; Aijun Zhang; Liangsheng Shi; Yuanyuan Zha; Honggen Xu; Hongye Yang; Xun Yu; Yi Bai; Shuaibing Liu; Minghan Cheng; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

Management‐induced changes in soil organic carbon and related crop yield dynamics in China's cropland - Bai‐Jian Lin; Ruo‐Chen Li; Ke‐Chun Liu; Olatunde Pelumi Oladele; Zhi‐Yu Xu; Rattan Lal; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2023)
Enhancing soil organic carbon (SOC) sequestration and food supply are vital for human survival when facing climate change. Site‐specific best management practices (BMPs) are being promoted for adoption globally as solutions. However, how SOC and crop yield are related to each other in responding to BMPs remains unknown. Here, path analysis based on meta‐analysis and machine learning was conducted to identify the effects and potential mechanisms of how the relationship between SOC and crop yield responds to site‐specific BMPs in China. The results showed that BMPs could significantly enhance SOC and maintain or increase crop yield. The maximum benefits in SOC (30.6%) and crop yield (79.8%) occurred in mineral fertilizer combined with organic inputs (MOF). Specifically, the optimal SOC and crop yield would be achieved when the areas were arid, soil pH was ≥7.3, initial SOC content was ≤10 g kg −1 , duration was >10 years, and the nitrogen (N) input level was 100–200 kg ha −1 . Further analysis revealed that the original SOC level and crop yield change showed an inverted V‐shaped structure. The association between the changes in SOC and crop yield might be linked to the positive role of the nutrient‐mediated effect. The results generally suggested that improving the SOC can strongly support better crop performance. Limitations in increasing crop yield still exist due to low original SOC level, and in regions where the excessive N inputs, inappropriate tillage or organic input is inadequate and could be diminished by optimizing BMPs in harmony with site‐specific conditions.

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Integrating Ecosystem Health and Services for Assessing Ecological Risk and its Response to Typical Land-Use Patterns in the Eco-fragile Region, North China - Yisen Wang; Zhonghua Yang; Minghui Yu; Ruyu Lin; Lei Zhu; Fengpeng Bai (Environmental Management, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Simultaneous dual-defect engineering as a booster for polysulfide adsorption and conversion in Li-S battery - Meixiu Qu; Yu Bai; Weiwei Yang; Lin Peng; Zhenhua Wang; Wang Sun; Kening Sun (Chemical Engineering Journal, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Gut as the target tissue of mercury and the extraintestinal effects - Xue Tian; Xiaoying Lin; Jiating Zhao; Liwei Cui; Yuxi Gao; Yong-Liang Yu; Bai Li; Yu-Feng Li (Toxicology, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Hollow Co-CeO2@PEG nanospheres: Ultrasound enhanced cascade-nanozyme for synergetic anticancer - Miao Wang; Stephen Choi; Qingchen Bai; Kai Yu; Wei Guo; Feng Zhang; Ran Jia; Fengyu Qu; Huiming Lin (Chemical Engineering Journal, 2023)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Rhodohalobacter sulfatireducens sp. nov., isolated from a marine solar saltern - Yu-Sheng Wang; Yu-Yan Yue; Yi-Lin Bai; Xu-Yang Zhang; Shuo Wang; Zong-Jun Du (Archives of Microbiology, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Contraction and warming of Antarctic Bottom Water in the Amundsen Sea - Yu Bai; Liang Zhao; Jingen Xiao; Shiying Lin (Acta Oceanologica Sinica, 2022)

Correction to: Comparative chloroplast genomes of Prunus subgenus Cerasus (Rosaceae): insights into sequence variations and phylogenetic relationships - Jiawen Yan; Jianhui Li; Lin Yu; Wenfu Bai; Dongling Nie; Ying Xiong; Sizheng Wu (Tree Genetics & Genomes, 2022)

Identifying the priority areas for enhancing the ecosystem services in hilly and mountainous areas of southern China - Jia-ling Tian; Yu Peng; Yi-hang Huang; Ting Bai; Lian-lin Liu; Xiao-ao He; Shi-qian Luo (Journal of Mountain Science, 2022)

Comparative chloroplast genomes of Prunus subgenus Cerasus (Rosaceae): insights into sequence variations and phylogenetic relationships - Jiawen Yan; Jianhui Li; Lin Yu; Wenfu Bai; Dongling Nie; Ying Xiong; Sizheng Wu (Tree Genetics & Genomes, 2021)

Temporal stability analysis of soil moisture along a coniferous forest hillslope with subtropical monsoon climate in southwest China - Yu-shi Bai; Mu-xing Liu; Jun Yi; Hai-lin Zhang (Journal of Mountain Science, 2021)

A new monoterpene-lactone with neuroprotective activity from corn silk - Wei-Yu Zhou; Tian-Ming Lv; Zi-Lin Hou; Ming Bai; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

GABA Signaling Pathway-associated Gene PLCL1 Rare Variants May be Associated with Autism Spectrum Disorders - Fengyun Zheng; Guoyuan Liu; Ting Dang; Qiaowen Chen; Yu An; Meng Wu; Xiangxuan Kong; Zilong Qiu; Bai-Lin Wu (Neuroscience Bulletin, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

Development of 85 SNP markers for the endangered plant species Prunus mira (Rosaceae) based on restriction site-associated DNA sequencing (RAD-seq) - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Yu-e Bai (Conservation Genetics Resources, 2020)

Diagnostic value of optic disc retinal nerve fiber layer thickness for diabetic peripheral neuropathy - Xiao-hong Wu; Jing-wen Fang; Yin-qiong Huang; Xue-feng Bai; Yong Zhuang; Xiao-yu Chen; Xia-hong Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Development and characterization of 72 SNP markers in Armeniaca sibirica based on transcriptomics - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Shulan Bai; Yu-e Bai (Conservation Genetics Resources, 2020)

Drought-tolerant plant growth-promoting rhizobacteria isolated from jujube (Ziziphus jujuba) and their potential to enhance drought tolerance - Min Zhang; Lin Yang; Ruqian Hao; Xiaoxiong Bai; Ying Wang; Xuan Yu (Plant and Soil, 2020)

Two new steroidal saponins from Maianthemum henryi and their cytotoxic activity against human HepG2 tumor cells - Jie Lin; Guoquan Wang; Lu Bai; Linzhong Yu (Natural Product Research, 2019)

Regulation of mitochondrial NAD pool via NAD+ transporter 2 is essential for matrix NADH homeostasis and ROS production in Arabidopsis - Lilan Luo; Yajun He; Yannan Zhao; Qian Xu; Jian Wu; Haiyan Ma; Hongyan Guo; Lin Bai; Jianru Zuo; Jian-Min Zhou; Hong Yu; Jiayang Li (Science China Life Sciences, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Polymorphism of duck MHC class molecules - Lin Zhang; Dongmei Lin; Sen Yu; Junping Bai; Wanchun Jiang; Wenzheng Su; Yanyan Huang; Shaohua Yang; Jiaqiang Wu (Immunogenetics, 2019)

Study on the bio-function of lipA gene in Aspergillus flavus - Wenzhao Bai; Tiejun Feng; Faxiu Lan; Guanglan Lin; Yu Li; Opemipo Esther Fasoyin; Yaju Liu; Kunzhi Jia (Genes & Genomics, 2019)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Spatiotemporal expression of proprotein convertase subtilisin/kexin type 5 in the development of anorectal malformations in fetal rats - Xiao Bing Tang; Li Chen; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Journal of Molecular Histology, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Comparison of ultrastructural and physiological changes of potato (Solanum tuberosum L.) plantlets subjected to salt and modeling drought stresses - Jiang-Ping Bai; Hui-Juan Gao; Hong-Yu Yang; Yan Lou; Jun-Lian Zhang; Di Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2016)

Genetic architecture, epigenetic influence and environment exposure in the pathogenesis of Autism - Li Yu; YiMing Wu; Bai-Lin Wu (Science China Life Sciences, 2015)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Predisposition to Behçet’s disease and VKH syndrome by genetic variants of miR-182 - Hongsong Yu; Yunjia Liu; Lin Bai; Aize Kijlstra; Peizeng Yang (Journal of Molecular Medicine, 2014)

Temporal and spatial expression of caudal-type homeobox gene-2 during hindgut development in rat embryos with ethylenethiourea-induced anorectal malformations - Xiao Bing Tang; Tao Zhang; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Cell and Tissue Research, 2014)

Akt and Erk1/2 activate the ornithine decarboxylase/polyamine system in cardioprotective ischemic preconditioning in rats: the role of mitochondrial permeability transition pores - Hao Zhang; Guo Xue; Weihua Zhang; Lina Wang; Hong Li; Li Zhang; Fanghao Lu; Shuzhi Bai; Yan Lin; Yu Lou; Changqing Xu; Yajun Zhao (Molecular and Cellular Biochemistry, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Expression of MMP-9 in hepatic sinusoidal obstruction syndrome induced by Gynura segetum - Xia-zhen Yu; Tao Ji; Xue-li Bai; Liang Liang; Lin-yan Wang; Wei Chen; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

Urban Phosphorus Metabolism through Food Consumption - Gui‐Lin Li; Xuemei Bai; Shen Yu; Hua Zhang; Yong‐Guan Zhu (Journal of Industrial Ecology, 2012)
Summary Urbanization has significant impacts on local, regional, and global biogeochemical cycles, including through nutrient enrichment by food consumption, and especially in rapidly urbanizing countries. This article presents a time‐series estimation of phosphorus (P) metabolism through food consumption in Chinese cities and examines its relationship to income level during the period 1985–2006. Our results show that approximately 39% of the total dietary P inflow is exported through direct sewage discharge without treatment, 35% is exported via the output of solid human excreta, 7% is exported through sewage sludge landfill, and 19% is left within urban areas. The total inflow of dietary P to urban systems increases with per capita disposable income level. Furthermore, the ratio of dietary P remaining in urban systems to total dietary P inflow, the dietary P remaining in urban systems per capita, and the dietary P remaining per unit urban built‐up area respond in an inverted U shape to increases in per capita disposable income; the per capita outflow of dietary P shows a U‐shaped response. These relationships may indicate that the impact of urban dietary P on urban environmental systems follows the traditional environmental Kuznets curve, while the environmental impact of urban dietary P on surrounding nonurban ecosystems initially decreases but then increases with the rising income of urban residents.

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Life cycle assessment of switchgrass-derived ethanol as transport fuel - Yu Bai; Lin Luo; Ester van der Voet (The International Journal of Life Cycle Assessment, 2010)

A ThCAP gene from Tamarix hispida confers cold tolerance in transgenic Populus (P. davidiana × P. bolleana) - Xiao-Hong Guo; Jing Jiang; Shi-Jie Lin; Bai-Chen Wang; Yu-Cheng Wang; Gui-Feng Liu; Chuan-Ping Yang (Biotechnology Letters, 2009)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)